Application of Self-Organized Learning Environment Model in Increasing Students’ Curiosity on Global Warming Topic in Senior High School - Basri, Nanda Ardita; Fauza, Naila; Lestari , Lutfi Rindang (Journal of Indonesian Science Teachers, 2024)
This research aims to describe high school students' curiosity about the topic of global warming. The type of research used is quasi-experimental. The research sample consisted of 35 students from group X-2 as the experimental group and 36 students from group X-3 as the control group. The instrument used in this research was a student curiosity questionnaire with 25 statement items which were divided into several indicators, namely the desire to learn something, a strong attitude to know something, and interest in new things. The descriptive analysis pointed out that our results show the average value of curiosity in the experimental group (0.82) is in the very good category compared to the control group (0.74) in the good category. The difference is significant according to inferential analysis, obtaining a significance value of 0.000 < 0.05. The conclusion obtained is that the use of the SOLE model can increase students' curiosity better in learning physics on global warming material at SMA Negeri 1 Kandis.